Peran Perempuan Dalam Meningkatkan Ketahanan Pangan Rumah Tangga Di Provinsi Nusa Tenggara Barat - Triana Pujilestari; Tri Haryanto (MediaTrend, 2020)
Food security at the national or regional level does not ensure food security at the household level. The study aim to analyze the influence of economic, demographic and social characteristics including the level of mother's education, mother's age, mother's occupation, access to the internet, household size, residential area, and household expenditure on the food security household level at NTB Province. Based on the data of The National Socioeconomic Survey (SUSENAS) March 2018 from Statistics Indonesia (BPS), this study is conducted by using multinomial logistic regression method to archieve the objective. The results show that the level of mother's education, mother's age, access to the internet, household size and household expenditure have significant effect to the food security household level at NTB province.